Gaya Bahasa dan Pemilihan Kata pada Podcast Rintik Sedu Episode “Kita Yang Terlupa” - Rahmahwati, Nadhila Zahra; Hindun, Hindun; Yundiani, Sri (Universitas Tidar, 2025)
Language style or what we know as rhetoric is style. Language style is a distinctive way of expressing thoughts and feelings in written or oral form. Even though the choice of diction is correct, if the language style used is not interesting, then the diction is useless. This research aims to describe the rhetoric, diction and language style in the Rintik Sedu Podcast